PERTUMBUHAN BIBIT TREMBESI (Samanea saman) DENGAN INOKULASI CENDAWAN MIKORIZA ARBUSKULA PADA MEDIA BEKAS TEMPAT PEMBUANGAN AKHIR (TPA) KLOTOK KEDIRI - Ahmad Bashri; Budhi Utami; Poppy Rahmatika Primandiri (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Abstract- Waste is a complex problem that is common in urban areas. The aims of this research to study the seedlings growth of Samanea saman on landfills media of Klotok Kediri. Breeding experiments was conducted during June-November 2013 on passive landfills and Laboratory of Biological Plant Physiology UNP Kediri. The factors of this research consist of a media i.e soil-compost, landfills, and landfills-compost. The second factor consist of fertilizers i.e without fertilizers, NPK with recommended, and arbuscular mycorrhiza fungi. The observed data was a percentage of normal living plants, plant height, stem diameter, and number of leaves. The results of this research that the landfills and landfills-compost was reduced the growth of Samanea saman seedling up to 20%. Application of arbuscular mycorrhiza fungi (AMF) was helped growth seedling up to 100% on landfills and landfills-compost media. AMF was increased significantly of plant height, diameter growth, stem, and leaf number of Samanea saman seedling on the landfills. Keywords: Samanea saman, CMA, TPA Klotok